Preparation method of catalytic cracking aid for reducing coke yield and increasing diesel oil yield, catalytic cracking catalyst and preparation method thereof
By performing acidification and crystallization reaction in the catalyst and combining surfactant, the problem of difficult to take into account both the diesel yield and the coke yield in catalytic cracking is solved, which improves the diesel yield and reduces the coke yield, and enhances the catalyst's Cracking performance improves energy utilization efficiency.
Patent Information
- Application Number
- CN202310794511.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The prior art is difficult to simultaneously improve diesel yield and reduce coke yield during catalytic cracking, resulting in low energy utilization efficiency and high energy consumption.
By adding acidified slurry to the catalyst to the crystallization reaction, the pore structure of the catalyst is strengthened and the L acid acidity of the matrix is regulated to improve diesel yield and reduce coke yield. .
It achieves the balance between improving diesel yield and reducing coke yield during catalytic cracking, enhances the heavy oil macromolecule cracking performance of the catalyst, improves energy utilization efficiency and reduces energy consumption.
Abstract
Description
Technical Field
[0001] The invention relates to the field of petroleum catalytic cracking materials, and in particular to a preparation method of a catalytic cracking aid capable of reducing coke yield and increasing diesel production, a catalytic cracking catalyst and a preparation method thereof. Background Art
[0002] In recent years, with the transformation and upgrading of industries and the rapid development of new energy, the growth rate of China's refined oil consumption has slowed down significantly, and the apparent consumption of diesel has been declining year by year since 2015. Nevertheless, due to the influence of factors such as logistics and transportation, infrastructure, industry and mining, manufacturing, export quotas, and especially seasonal and policy factors, the demand for diesel has increased significantly with regional characteristics, leading to an increase in the production enthusiasm of independent refineries. Therefore, under the premise of unchanged raw materials and properties, it is of great significance to study catalytic cracking catalysts that reduce coke yield and increase diesel yield from the perspective of reducing carbon emissions, energy saving and consumption reduction to improve energy utilization efficiency, reduce energy consumption, and improve efficiency of refineries.
[0003] Diesel mainly includes straight-run diesel and secondary processed diesel. As my country's crude oil is heavy, it must be processed through secondary processing to achieve lightness of heavy crude oil. Diesel produced through secondary processing such as catalytic cracking, hydrocracking and delayed coking accounts for more than 60% of the total diesel, and catalytic diesel produced by catalytic cracking accounts for more than two-thirds of secondary processed diesel. At the same time, the catalytic cracking unit is flexible in operation, so improving the diesel yield of catalytic cracking is crucial to increasing the diesel output of refineries. In the process of catalytic cracking, the change and optimization of operating conditions and the use of high-yield diesel catalysts are the main measures to increase diesel production.
[0004] The diesel yield and diesel-to-gasoline ratio of the catalytic cracking unit increase with the decrease of conversion rate, but the total light oil yield decreases, while the heavy oil yield increases. Therefore, if the catalytic cracking unit wants to produce more diesel, it is necessary to properly control the conversion rate. However, changing the catalytic cracking operating parameters to increase diesel production is actually to reduce the re-cracking of the intermediate fraction by reducing the primary conversion rate to achieve the purpose of increasing the diesel yield. With the decrease of the primary conversion rate, the unit's processing capacity will also decrease, the coke yield will increase, and the gas production will increase. In addition to the adjustment of the operating process, the catalyst, as the core technology of catalytic cracking, adjusts the pore distribution on the active components and the matrix, as well as the density, strength and type of the acid center, which has a very important influence on improving the diesel selectivity.
[0005] For example, Chinese patent document CN108499600A discloses a catalytic cracking catalyst for producing more diesel and its preparation method. By using non-phosphoric acid boron-containing boron substances to adjust the catalyst acidic structure, the invented catalyst has a high diesel yield and resistance to heavy metal pollution. Chinese patent document CN110479362A regulates the acidity and alkalinity of Y molecular sieve, modifies MFI molecular sieve and matrix, and increases the relative content of matrix to achieve the effect of producing more propylene and diesel at the same time. Chinese patent document CN103861636A effectively controls the peptization degree of pseudo-boehmite and increases the pore volume of the catalyst, thereby improving the heavy oil cracking ability and diesel yield of the catalyst. Chinese patent document CN103506148A uses magnesium element to modify ultra-stable Y-type molecular sieve, and adjusts the acid strength of the molecular sieve to reduce coke and increase the diesel yield. Chinese patent document CN100413941C discloses a catalytic cracking promoter that does not contain a zeolite component and produces more diesel. The spray microspheres containing kaolin, pseudo-boehmite, and water glass are calcined at high temperature, extracted into channels by strong alkalis such as sodium hydroxide, and finally loaded with phosphorus and rare earths to prepare the promoter. In practical applications, the diesel yield of the FCC catalytic device can be increased without changing the catalyst originally used in the oil refining device, improving product distribution, and improving the utilization rate of existing catalyst varieties. The catalytic cracking promoter disclosed in Chinese patent document CN102974335A contains mesoporous silicon-aluminum materials and clay and / or heat-resistant inorganic oxides. The diesel yield of the catalyst prepared by the promoter is 16%-17%, and the conversion rate of coke is less than 0.1%. The catalytic cracking aid disclosed in Chinese patent document CN104492472A includes mixing, aging, spraying and calcining the SBA-15 raw powder containing a template or the SBA-15 raw powder containing a template introduced with magnesium salt, a binder and a matrix, and finally obtaining the microspherical fluidized catalytic cracking catalyst aid, which is suitable for catalytic cracking processing of heavy distillate oil raw materials, reducing the coke yield while increasing the yield of gasoline and diesel components. However, while strengthening the catalyst pore structure, this technology does not effectively regulate the acidity of the matrix, resulting in an insignificant increase in diesel yield.
[0006] The use of a double aluminum-based bonding process can effectively improve the pore structure and acidity of the matrix, wherein aluminum sol is used to improve the strength of the catalyst, and pseudo-boehmite is introduced into the matrix to improve the pore structure of the catalyst carrier. For example, Chinese patent documents CN1436835 and Chinese patent documents CN1690168 found that by roasting pseudo-boehmite at 150-400°C, medium- and macroporous alumina can be obtained, so that the matrix of the catalyst has an open-pore structure, which increases the pore volume and pore diameter of the catalyst, strengthens the cracking of macromolecular heavy oil, thereby reducing the coke yield, and has a certain resistance to metal pollution. Chinese patent document CN1098130 uses a double aluminum bonding process to significantly improve the heavy oil cracking ability of the catalyst. After that, the double aluminum bonding process was further improved, and a new shallow acidification process was developed. The matrix was acidified under a lower acid-aluminum ratio, and the temperature aging process was cancelled. The colloidal particles formed loose accumulation due to incomplete peptization, thereby increasing the open pores, and at the same time, the proportion of aluminum sol in the double aluminum base was appropriately increased to increase the strength of the catalyst. Chinese patent document CN103506148A discloses a catalytic cracking catalyst that reduces coke yield and produces more diesel, comprising a modified Y-type molecular sieve, an ultra-stable Y-type molecular sieve containing magnesium, clay and an inorganic oxide binder; the modified Y-type molecular sieve catalyst contains a "triple cross-linked and triple roasted" phosphorus and rare earth modified Y-type molecular sieve, which can produce more diesel and reduce coke yield. Chinese patent document CN107433170A discloses a magnesium aluminum sol used as a binder in a catalytic cracking catalyst; the magnesium aluminum sol can also be modified with a phosphorus compound and / or a rare earth compound, and the final catalyst strength and activity meet the requirements for industrial use, and the catalyst wear index is significantly reduced.
[0007] In order to further improve the pore structure, a certain amount of pore distribution improver is added to the catalyst on the basis of the dual aluminum-based bonding process. For example, in Chinese patent document CN1293225 and Chinese patent document CN1388213, water glass is added as a pore distribution improver to make the matrix have more pores. The above technology is to introduce macroporous materials in the catalyst preparation process or strengthen its pore structure by shallowly acidifying pseudo-boehmite, or to strengthen the cracking of macromolecular heavy oil by adjusting the acidity of the molecular sieve. The purpose of introducing magnesium aluminum sol is to increase the solid content of the colloid, thereby reducing energy consumption and reducing production costs.
[0008] Although the above improvement scheme can improve the diesel yield or reduce the coke yield to a certain extent, it cannot achieve both high diesel yield and low coke yield. Summary of the invention
[0009] In view of the problems existing in the prior art and the areas that need improvement, the present invention provides a method for preparing a catalytic cracking aid that reduces coke yield and produces more diesel. When designing a catalyst for producing more diesel, the matrix is used to strengthen the catalyst pore structure while further regulating the acidity of the matrix L-acid, so as to solve the technical problem that it is difficult to achieve both high diesel yield and low coke yield in the prior art.
[0010] To achieve the above object, the present invention provides the following technical solutions:
[0011] A method for preparing a catalytic cracking aid for reducing coke yield and increasing diesel production comprises the following steps:
[0012] After mixing pseudo-boehmite and deionized water, an acidic substance is added for peptization treatment to obtain pseudo-boehmite slurry;
[0013] The pseudo-boehmite slurry is mixed with the magnesium oxide slurry, and then a surfactant is added to carry out a crystallization reaction to obtain the catalytic cracking aid for reducing the coke yield and increasing the diesel yield;
[0014] Wherein, the weight ratio of the pseudo-boehmite calculated on a dry basis of alumina to the magnesium oxide slurry calculated on a dry basis of magnesium oxide is (0.2-0.8):1;
[0015] The crystallization reaction temperature is 50-95°C and the time is 10-24h;
[0016] The mass ratio of the dry basis of the catalytic cracking aid to the surfactant is 1:0.01-0.05.
[0017] Optionally, in the method for preparing a catalytic cracking aid for reducing coke yield and increasing diesel production provided by the present invention, the mass ratio of the pseudo-boehmite, the acidic substance and the pseudo-boehmite is 0.05 to 0.25 based on dry alumina;
[0018] The temperature of the peptization treatment is 40-80° C. and the time is 1-3 hours.
[0019] Optionally, in the method for preparing a catalytic cracking aid for reducing coke yield and increasing diesel production provided by the present invention, the solid content of the pseudo-boehmite peptized is 0.15 to 0.25;
[0020] The magnesium oxide slurry is a mixed slurry of magnesium oxide and water, and the solid content of the magnesium oxide slurry is 0.2-0.4.
[0021] Optionally, in the method for preparing a catalytic cracking aid for reducing coke yield and increasing diesel production provided by the present invention, the surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride;
[0022] The acidic substance is selected from one or more of hydrochloric acid, nitric acid, formic acid and acetic acid;
[0023] The crystallization reaction is carried out in any one of static, dynamic or intermittent dynamic crystallization.
[0024] On this basis, the present invention provides a catalytic cracking catalyst, which comprises, based on the total mass of the catalytic cracking catalyst being 100%, 5wt% to 20wt% of a molecular sieve on a dry basis, 25wt% to 40wt% of an inorganic oxide binder on an oxide basis, 0 to 3wt% of a rare earth additive on an oxide basis, 5wt% to 15wt% of a magnesium aluminum matrix material on a dry basis, and 30wt% to 50wt% of a modified clay on a dry basis;
[0025] The magnesium-aluminum matrix material is the catalytic cracking aid for reducing coke yield and increasing diesel production obtained by the above-mentioned preparation method of the catalytic cracking aid for reducing coke yield and increasing diesel production.
[0026] Optionally, in the catalytic cracking catalyst provided by the present invention, the molecular sieve is selected from a Y-type molecular sieve or a modified product of a Y-type molecular sieve, and the modified product of the Y-type molecular sieve is selected from one or more of REUSY molecular sieve, HRSY-1 molecular sieve, RDSY molecular sieve and MASY molecular sieve.
[0027] Optionally, in the catalytic cracking catalyst provided by the present invention, the modified clay is acid-modified clay, and the method of modifying the clay with acid is not specifically limited, and the conventional method in the industry can be used, such as slurrying the clay with deionized water, stirring evenly at 60-70°C, adding an acidic substance and maintaining the pH value of the system between 0 and 2, and continuously stirring for not less than 1 hour to obtain acid-modified clay. The clay is selected from one or more of kaolin, halloysite, montmorillonite, sepiolite, hydrotalcite and rectorite;
[0028] The rare earth additive is a water-soluble rare earth compound, preferably one or more of chlorides or nitrates of lanthanum, cerium, praseodymium, neodymium and yttrium;
[0029] The inorganic oxide binder is one or more of aluminum sol, silica sol, pseudo-boehmite and silica-alumina sol.
[0030] The present invention also provides a method for preparing the above-mentioned catalytic cracking catalyst, comprising the following steps:
[0031] 1) adding an inorganic oxide binder to the modified clay and controlling the pH of the system to be 1-3; then adding a magnesium-aluminum matrix material and a molecular sieve to form a slurry;
[0032] 2) spray drying and calcining the slurry to obtain a solidified catalyst; washing and drying to obtain the catalytic cracking catalyst.
[0033] In the preparation method of the catalytic cracking catalyst provided by the present invention, the modified clay is acid-modified clay, and the specific modified preparation method is not limited, and the conventional method in the industry can be used, such as the following method:
[0034] After the clay is slurried with deionized water, it is stirred evenly at 60-70° C., and then an acidic substance such as hydrochloric acid, nitric acid or formic acid is added to maintain the pH value of the system between 0 and 2, and then the stirring is continued for not less than 1 hour to obtain modified clay.
[0035] Optionally, in the preparation method of the catalytic cracking catalyst provided by the present invention, the process of forming the slurry in step 1) also includes the step of adding a rare earth additive, that is, adding an inorganic oxide binder to the modified clay, and controlling the pH of the system to 1-3: then adding the magnesium aluminum matrix material, the rare earth additive and the molecular sieve to form a slurry.
[0036] Optionally, in the method for preparing the catalytic cracking catalyst provided by the present invention, the calcination and curing temperature is 300 to 600° C., and the time is 0.5 to 2 h;
[0037] An ammonium chloride aqueous solution is used for washing, and the washing temperature is 30-90° C.; preferably, the mass ratio of the cured catalyst to the ammonium chloride aqueous solution is 1:(2-10), and the mass ratio of ammonium chloride to water in the ammonium chloride aqueous solution is (1-10):100.
[0038] Optionally, in the preparation method of the catalytic cracking catalyst provided by the present invention, the slurry is dried by spray drying, and the specific spray drying parameters are not limited, and conventional parameters in the industry can be adopted, such as: inlet temperature 350-450°C, outlet temperature 120-200°C.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] A high-yield diesel catalyst should have a strong heavy oil cracking ability and a weak secondary cracking ability for the middle distillate, that is, it should have abundant medium and large pores, high acid content and medium-weak acid strength. Since the micropores of the catalyst mainly come from the molecular sieve, in order to reduce the micropore content in the catalyst and reduce the number of strong and weak acid sites in the micropores, a molecular sieve with suitable acidity should be used and its content in the catalyst should be reduced to reduce the re-cracking of the middle distillate. The mesopores of the catalyst mainly come from the matrix component. To increase the mesopore content, it is necessary to increase the alumina matrix in the catalyst, that is, the content of pseudo-boehmite. However, while increasing the alumina matrix, it also brings about an increase in the amount of strong Lewis acid in the catalyst, resulting in an increase in the catalyst's coking tendency. In the catalytic cracking process, the catalytic activity comes from the acidic centers on the surface of the molecular sieve, and Bronsted acid and Lewis acid exist in the molecular sieve. B acid is an acidic hydrocarbon group carried by the aluminum-oxygen tetrahedron on the molecular sieve framework. It follows the catalytic cracking reaction of positive carbon ions. L acid is mainly distributed in the catalyst matrix, molecular sieve defect sites and non-framework aluminum. The role of the matrix in heavy oil cracking is to crack large molecules into intermediate transition molecules. Weak L acid helps to initiate cracking. When the L acid is strong, it is easy to adsorb unsaturated hydrocarbons and difficult to desorb, causing dehydrogenation and comprehensive reactions, and finally generating coke. Therefore, while strengthening the catalyst pore structure through the matrix, how to regulate the matrix L acid acidity, thereby increasing the diesel yield while reducing the coke yield is a difficult point.
[0041] Beneficial effect 1: The present invention obtains a catalytic cracking aid by mixing acidified pseudo-boehmite with magnesium oxide slurry (a mixture of magnesium oxide and water), and then crystallizing it under the action of a surfactant. The catalyst prepared by using the catalytic cracking aid can increase the content of alumina matrix and the number of mesopores while reducing the molecular sieve content and the acid content; the catalytic cracking aid can control the amount of strong Lewis acid in the catalyst matrix, avoid the number of strong Lewis acid sites that tend to produce coke, reduce the coke yield, and increase the yield of diesel.
[0042] Beneficial effect 2: The catalytic cracking catalyst provided by the present invention adopts the magnesium-aluminum matrix material prepared by the method provided by the present invention, combined with modified clay, molecular sieve and inorganic oxide binder, etc., and the components cooperate with each other, while increasing the number of macropores and introducing an appropriate amount of Bronsted acid, which can further enhance its heavy oil macromolecular sieve cracking performance; at the same time, combined with resistance to heavy metals and optimized pore structure of the catalyst, the coke yield of the catalyst can be reduced while increasing diesel production. DETAILED DESCRIPTION
[0043] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0044] Example 1
[0045] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0046] Take 161 grams of pseudo-boehmite, add 505 grams of deionized water, add 10 grams of concentrated hydrochloric acid with a concentration of 36% to 38% under continuous stirring, and then heat to 40°C and maintain for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0047] Take 20 grams of magnesium oxide, add 50 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 1.2 grams of hexadecyltrimethylammonium bromide, beat and mix for 30 minutes to obtain magnesium aluminum colloidal slurry;
[0048] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 50° C. for 72 hours to obtain a magnesium-aluminum matrix material (i.e., a catalytic cracking aid). In the material, m(magnesium oxide):m(aluminum oxide)=0.2:1.
[0049] (2) Preparation of Catalyst
[0050] Take 1047 grams of kaolin, add 2412 grams of deionized water, add 210 grams of concentrated hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 60 minutes to obtain modified clay; then add 806 grams of pseudo-boehmite, at this time the system pH = 2.5, stir for 60 minutes; add 240 grams of magnesium aluminum matrix material slurry prepared in step (1), then add 506 grams of RDSY molecular sieve, 102 grams of HRSY-1 molecular sieve and 1059 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry at an inlet temperature of 350°C and an outlet temperature of 120°C, solidify and roast at 400°C for 2 hours, then take 500 grams of the solidified and roasted microspheres, use a solution formed by 2500 grams of deionized water and 25 grams of ammonium chloride, wash at 60°C for 30 minutes, filter and dry to obtain a catalytic cracking catalyst. It is denoted as S1, and the reaction performance is shown in Table 1.
[0051] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (magnesium aluminum matrix material): m (modified clay) = 25%: 26%: 5%: 44%.
[0052] Example 2
[0053] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0054] Take 161 grams of pseudo-boehmite, add 339 grams of deionized water, add 15 grams of 99% formic acid under continuous stirring, raise the temperature to 50°C and keep for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0055] Take 30 grams of magnesium oxide, add 45 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 2.6 grams of hexadecyltrimethylammonium bromide, beat and mix for 30 minutes to obtain magnesium aluminum colloidal slurry;
[0056] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 95° C. for 10 hours to obtain a magnesium-aluminum matrix material in which m(magnesium oxide):m(aluminum oxide)=0.3:1.
[0057] (2) Preparation of Catalyst
[0058] Take 905 grams of kaolin, add 2770 grams of deionized water, add 201 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 65°C and continue stirring for 60 minutes to obtain modified clay; then add 968 grams of pseudo-boehmite, at which time the system pH is 2.5, and stir for 60 minutes; add 800 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 506 grams of RDSY molecular sieve, 40 grams of lanthanum chloride and 854 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of an inlet temperature of 380°C and an outlet temperature of 150°C, and solidify and roast it at 350°C for 1 hour. Then take 500 grams of the solidified and roasted microspheres, use a solution formed by 2000 grams of deionized water and 40 grams of ammonium chloride, wash it at 80°C for 30 minutes, filter and dry it, and obtain a catalytic cracking catalyst. It is denoted as S2, and the reaction performance is shown in Table 1.
[0059] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 20%: 31%: 1%: 10%: 38%.
[0060] Example 3
[0061] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0062] Take 161 g of pseudo-boehmite, add 239 g of deionized water, add 15 g of 99% acetic acid under continuous stirring, raise the temperature to 60° C. and maintain for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0063] Take 50 grams of magnesium oxide, add 75 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 4.5 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0064] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 80° C. for 24 hours to obtain a magnesium-aluminum matrix material, in which m (magnesium oxide): m (aluminum oxide) = 0.5:1.
[0065] (2) Preparation of Catalyst
[0066] Take 928 grams of kaolin, add 3841 grams of deionized water, add 262 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 60°C and continue stirring for 70 minutes to obtain modified clay; then add 1129 grams of pseudo-boehmite, at which time the system pH is 2.1, and stir for 60 minutes; add 800 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 305 grams of HRSY-1 molecular sieve, 40 grams of praseodymium chloride and 721 grams of deionized water, mix and stir evenly, and obtain a slurry, spray dry it under the conditions of an inlet temperature of 400°C and an outlet temperature of 150°C, and solidify and roast it at 450°C for 1 hour, then take 500 grams of the solidified and roasted microspheres, use a solution formed by 2000 grams of deionized water and 80 grams of ammonium chloride, wash it at 90°C for 30 minutes, filter and dry it, and obtain a catalytic cracking catalyst. It is denoted as S3, and the reaction performance is shown in Table 1.
[0067] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 15%: 35%: 1%: 10%: 39%.
[0068] Example 4
[0069] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0070] Take 161 grams of pseudo-boehmite, add 239 grams of deionized water, add 15 grams of nitric acid with a concentration of 65% to 68% under continuous stirring, heat to 60°C and keep for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0071] Take 80 grams of magnesium oxide, add 187 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, then add 9 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0072] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 70° C. for 36 hours to obtain a magnesium-aluminum matrix material, in which m (magnesium oxide): m (aluminum oxide) = 0.8:1.
[0073] (2) Preparation of Catalyst
[0074] Take 1119 grams of halloysite, add 3904 grams of deionized water, add 318 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 90 minutes to obtain modified clay; then add 968 grams of pseudo-boehmite, at which time the system pH is 1.8, and stir for 60 minutes; add 960 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 204 grams of HRSY-1 molecular sieve, 28 grams of yttrium nitrate and 500 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of an inlet temperature of 420°C and an outlet temperature of 180°C, and solidify and roast it at 450°C for 1 hour. Then take 500 grams of the solidified and roasted microspheres, use a solution formed by 2000 grams of deionized water and 200 grams of ammonium chloride, wash it at 70°C for 30 minutes, filter and dry it, and obtain a catalytic cracking catalyst. It is denoted as S4, and the reaction performance is shown in Table 1.
[0075] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 10%: 30%: 1%: 12%: 47%.
[0076] Example 5
[0077] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0078] Take 161 grams of pseudo-boehmite, add 239 grams of deionized water, add 20 grams of nitric acid with a concentration of 65% to 68% under continuous stirring, heat to 80°C and keep for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0079] Take 20 grams of magnesium oxide, add 60 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 4.2 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0080] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 90° C. for 18 hours to obtain a magnesium-aluminum matrix material, in which m (magnesium oxide): m (aluminum oxide) = 0.2:1.
[0081] (2) Preparation of Catalyst
[0082] Take 881 grams of sepiolite, add 3904 grams of deionized water, add 248 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 80 minutes to obtain modified clay; then add 1290 grams of silica sol, at this time the system pH = 2.0, stir for 60 minutes; add 1200 grams of magnesium aluminum matrix material slurry prepared in step (1), then add 126 grams of RDSY molecular sieve, 129 grams of neodymium nitrate and 310 grams of deionized water, mix and stir evenly, obtain slurry, spray dry under the conditions of inlet temperature 450°C and outlet temperature 200°C, solidify and roast at 500°C for 0.5 hours, then take 500 grams of microspheres after solidification and roasting, use 2000 grams of deionized water and 100 grams of ammonium chloride to form a solution, wash at 45°C for 30 minutes, filter and dry to obtain catalytic cracking catalyst. It is denoted as S5, and the reaction performance is shown in Table 1.
[0083] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 5%: 40%: 3%: 15%: 37%.
[0084] Example 6
[0085] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0086] Take 161 grams of pseudo-boehmite, add 339 grams of deionized water, add 25 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 80°C and keep for 2 hours to obtain a peptized pseudo-boehmite slurry;
[0087] Take 50 grams of magnesium oxide, add 120 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, then add 6 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0088] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 95° C. for 48 hours to obtain a magnesium-aluminum matrix material, in which m (magnesium oxide): m (aluminum oxide) = 0.5:1.
[0089] (2) Preparation of Catalyst
[0090] Take 1190 grams of montmorillonite, add 3904 grams of deionized water, add 336 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 60 minutes to obtain modified clay; then add 806 grams of aluminum sol, at this time the system pH = 2.7, stir for 60 minutes; add 1040 grams of magnesium aluminum matrix material slurry prepared in step (1), then add 253 grams of MASY molecular sieve, 80 grams of lanthanum chloride and 467 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of inlet temperature 420°C and outlet temperature 150°C, solidify and roast it at 500°C for 0.5 hours, then take 500 grams of the solidified and roasted microspheres, use a solution formed by 3000 grams of deionized water and 200 grams of ammonium chloride, wash it at 80°C for 30 minutes, filter and dry it to obtain a catalytic cracking catalyst. It is denoted as S6, and the reaction performance is shown in Table 1.
[0091] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 10%: 25%: 2%: 13%: 50%.
[0092] Example 7
[0093] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0094] Take 161 grams of pseudo-boehmite, add 257 grams of deionized water, add 15 grams of nitric acid with a concentration of 65% to 68% under continuous stirring, raise the temperature to 75°C and maintain for 3 hours to obtain a peptized pseudo-boehmite slurry;
[0095] Take 60 grams of magnesium oxide, add 137 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 6 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0096] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 95° C. for 18 hours to obtain a magnesium-aluminum matrix material, in which m(magnesium oxide):m(aluminum oxide)=0.6:1.
[0097] (2) Preparation of Catalyst
[0098] Take 1012 grams of kaolin, add 3633 grams of deionized water, add 285 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 90 minutes to obtain modified clay; then add 903 grams of pseudo-boehmite, at which time the system pH is 1.5, and stir for 60 minutes; add 1200 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 329 grams of REUSY molecular sieve, 60 grams of lanthanum chloride and 578 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of an inlet temperature of 420°C and an outlet temperature of 160°C, and solidify and roast it at 550°C for 0.5 hours. Then take 500 grams of the solidified and roasted microspheres, use a solution formed by 5000 grams of deionized water and 200 grams of ammonium chloride, wash it at 35°C for 30 minutes, filter and dry it, and obtain a catalytic cracking catalyst. It is denoted as S7, and the reaction performance is shown in Table 1.
[0099] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 13%: 28%: 1.5%: 15%: 42.5%.
[0100] Comparative Example 1
[0101] Catalyst preparation
[0102] Take 1143 grams of kaolin, add 2770 grams of deionized water, add 201 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 65°C and continue stirring for not less than 60 minutes to obtain modified clay; then add 968 grams of pseudo-boehmite, at this time the system pH = 2.5, stir for 60 minutes; then add 506 grams of RDSY molecular sieve, 40 grams of lanthanum chloride and 854 grams of deionized water, mix and stir evenly, obtain slurry, spray dry under the conditions of inlet temperature 380°C and outlet temperature 150°C, solidify and roast at 350°C for 1 hour, then take 500 grams of solidified and roasted microspheres, use 2000 grams of deionized water and 40 grams of ammonium chloride to form a solution, wash at 80°C for 30 minutes, filter and dry to obtain a catalytic cracking catalyst. It is recorded as D1, and the reaction performance is shown in Table 1.
[0103] In the catalytic cracking catalyst prepared in this comparative example, the molecular sieve and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m(molecular sieve):m(inorganic oxide binder):m(rare earth additive):m(modified clay)=20%:31%:1%:48%.
[0104] Comparative Example 2
[0105] Catalyst preparation
[0106] Take 905 grams of kaolin, add 2770 grams of deionized water, add 201 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 65°C and continue stirring for not less than 60 minutes to obtain modified clay; then add 968 grams of pseudo-boehmite, then add 151 grams of magnesium chloride and 2000 grams of deionized water, stir for 60 minutes; then add 506 grams of RDSY molecular sieve, 40 grams of lanthanum chloride and 854 grams of deionized water, mix and stir evenly, and obtain a slurry, which is spray-dried at an inlet temperature of 380°C and an outlet temperature of 150°C, and cured and calcined at 350°C for 1 hour, and then take 500 grams of the cured and calcined microspheres, use a solution formed by 2000 grams of deionized water and 40 grams of ammonium chloride, wash at 80°C for 30 minutes, filter and dry, and obtain a catalytic cracking catalyst. It is recorded as D2, and the reaction performance is shown in Table 1.
[0107] In the catalytic cracking catalyst prepared in this comparative example, the molecular sieve and modified clay, calculated on a dry basis, and the inorganic oxide binder, magnesium chloride and rare earth additive, calculated on an oxide basis, are m(molecular sieve):m(inorganic oxide binder):m(magnesium oxide):m(rare earth additive):m(modified clay)=20%:31%:1.5%:1%:46.5%.
[0108] Comparative Example 3
[0109] (1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0110] Take 161 grams of pseudo-boehmite, add 257 grams of deionized water, add 15 grams of nitric acid with a concentration of 65% to 68% under continuous stirring, raise the temperature to 75°C and maintain for 3 hours to obtain a peptized pseudo-boehmite slurry;
[0111] Take 60 grams of magnesium oxide, add 137 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, and then add 6 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloid, and set aside;
[0112] In the magnesium-aluminum colloid, m(magnesium oxide):m(aluminum oxide)=0.6:1.
[0113] (2) Preparation of Catalyst
[0114] Take 1012 grams of kaolin, add 3633 grams of deionized water, add 285 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 90 minutes to obtain modified clay; then add 903 grams of pseudo-boehmite, at which time the system pH is 1.5, and stir for 60 minutes; add 1200 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 329 grams of REUSY molecular sieve, 60 grams of lanthanum chloride and 578 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of an inlet temperature of 420°C and an outlet temperature of 160°C, and solidify and roast it at 550°C for 0.5 hours. Then take 500 grams of the solidified and roasted microspheres, use a solution formed by 5000 grams of deionized water and 200 grams of ammonium chloride, wash it at 35°C for 30 minutes, filter and dry it, and obtain a catalytic cracking catalyst. It is recorded as D3, and the reaction performance is shown in Table 1.
[0115] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 13%: 28%: 1.5%: 15%: 42.5%.
[0116] Comparative Example 4
[0117] 1) Preparation of magnesium-aluminum matrix material (catalytic cracking aid)
[0118] Take 161 grams of pseudo-boehmite, add 239 grams of deionized water, add 15 grams of nitric acid with a concentration of 65% to 68% under continuous stirring, heat to 60°C and keep for 1 hour to obtain a peptized pseudo-boehmite slurry;
[0119] Take 80 grams of magnesium oxide, add 187 grams of deionized water, mix well, and obtain magnesium oxide slurry; add the magnesium oxide slurry to the above-mentioned pseudo-boehmite slurry, then add 9 grams of hexadecyltrimethylammonium chloride, beat and mix for 60 minutes to obtain magnesium aluminum colloidal slurry;
[0120] The magnesium-aluminum colloidal slurry was transferred to a crystallization reactor for crystallization reaction at 70° C. for 5 hours to obtain a magnesium-aluminum matrix material, in which m (magnesium oxide): m (aluminum oxide) = 0.8:1.
[0121] (2) Preparation of Catalyst
[0122] Take 1119 grams of halloysite, add 3904 grams of deionized water, add 318 grams of hydrochloric acid with a concentration of 36% to 38% under continuous stirring, heat to 70°C and continue stirring for 90 minutes to obtain modified clay; then add 968 grams of pseudo-boehmite, at which time the system pH is 1.8, and stir for 60 minutes; add 960 grams of the magnesium-aluminum matrix material slurry prepared in step (1), then add 204 grams of HRSY-1 molecular sieve, 28 grams of yttrium nitrate and 500 grams of deionized water, mix and stir evenly, and obtain a slurry. Spray dry it under the conditions of an inlet temperature of 420°C and an outlet temperature of 180°C, and solidify and roast it at 450°C for 1 hour. Then take 500 grams of the solidified and roasted microspheres, use a solution formed by 2000 grams of deionized water and 200 grams of ammonium chloride, wash it at 70°C for 30 minutes, filter and dry it to obtain a catalytic cracking catalyst. It is denoted as D4, and the reaction performance is shown in Table 1.
[0123] In the catalytic cracking catalyst prepared in this embodiment, the molecular sieve, magnesium aluminum matrix material and modified clay, calculated on a dry basis, and the inorganic oxide binder and rare earth additive, calculated on an oxide basis, are m (molecular sieve): m (inorganic oxide binder): m (rare earth additive): m (magnesium aluminum matrix material): m (modified clay) = 10%: 30%: 1%: 12%: 47%.
[0124] Catalyst Evaluation:
[0125] The element contents in the catalyst were determined by X-ray fluorescence analysis.
[0126] ACE was used to evaluate the reaction performance of catalytic cracking catalysts. The catalyst sample was placed in the reactor of the ACE experiment, with a reaction temperature of 530°C, a regeneration temperature of 685°C, a feed amount of 1.80 g, a cold trap temperature of -13.5°C, and a catalyst-to-oil ratio of 5.0. The product distribution and conversion rate after the reaction were analyzed and calculated.
[0127] Based on the heavy oil conversion rate, the selectivity of the catalyst for diesel in the catalytic cracking reaction is expressed by the following mathematical formula:
[0128] DI = (diesel yield / heavy oil yield) × (diesel yield / coke yield)
[0129] The larger the DI, the better the diesel selectivity of the catalyst.
[0130] Table 1 Catalyst ACE evaluation results
[0131] catalyst S1 S2 S3 S4 S5 S6 S7 D1 D2 D3 D4 Coke 5.36 5.02 4.85 4.51 4.21 4.36 4.75 5.68 5.86 5.47 5.71 Dry gas 2.54 2.35 2.21 2.15 2.02 2.87 2.21 2.78 2.85 2.56 2.58 gasoline 37.82 32.5 30.31 29.01 23.43 28.89 28.56 39.25 32.2 24 24.1 diesel fuel 25.06 27.85 29.24 30.25 35.21 30.24 30.12 22.29 20.23 20.35 19.25 heavy oil 20.14 23.54 25.41 26.57 28.62 26.15 26.85 20.14 30.35 40.21 41.21 LPG 9.08 8.74 7.98 7.51 6.51 7.49 7.51 9.86 8.51 7.41 7.15 100 100 100 100 100 100 100 100 100 100 100 Conversion rate 54.8 48.61 45.35 43.18 36.17 43.61 43.03 57.57 49.42 39.44 39.54 DI 5.818 6.564 6.938 7.636 10.289 8.021 7.113 4.343 2.301 1.883 1.575
[0132] From the data in the above table, it can be seen that S1-S7 all showed higher diesel yield and lower coke yield, maintaining excellent coke selectivity (coke selectivity = coke yield / conversion rate) and diesel selectivity (diesel selectivity = diesel yield / heavy oil yield) × (diesel yield / coke yield).
[0133] In the preparation process of Comparative Example 1, no magnesium-aluminum matrix material was introduced. Although its conversion rate was high, the diesel yield was low and the coke yield was high, and it did not show high diesel selectivity. In Comparative Example 2, compared with Comparative Example 1, magnesium chloride was introduced in the preparation process, but the alkali metal magnesium neutralized part of the acid center of the catalyst, resulting in a decrease in the conversion rate. In Comparative Examples 3 and 4, the magnesium-aluminum matrix material showed properties similar to those of the free magnesium component, neutralized a large amount of the catalyst acid center, and the conversion rate was further reduced.
[0134] The above embodiments are typical examples listed to illustrate the technical solutions of the present invention in detail. The present invention is subject to the protection scope of the claims and the content of the invention and is not limited by the implementation scheme. Simple replacement or modification of the present invention is still within the protection scope of the present invention.
Claims
1. A method for preparing a catalytic cracking aid for reducing coke yield and increasing diesel production, characterized in that: The steps include: After mixing pseudo-boehmite and deionized water, an acidic substance is added for peptization treatment to obtain pseudo-boehmite slurry; The pseudo-boehmite slurry is mixed with the magnesium oxide slurry, and then a surfactant is added to carry out a crystallization reaction to obtain the catalytic cracking aid for reducing the coke yield and increasing the diesel yield; Wherein, the weight ratio of the pseudo-boehmite calculated on a dry basis of alumina to the magnesium oxide slurry calculated on a dry basis of magnesium oxide is (0.2-0.8):1; The crystallization reaction temperature is 50-95°C and the time is 10-72h; The mass ratio of the dry basis of the catalytic cracking aid to the surfactant is 1:0.01-0.
05.
2. The preparation method according to claim 1, characterized in that The mass ratio of the pseudo-boehmite to the acidic substance is 0.05 to 0.25 based on dry alumina; The temperature of the peptization treatment is 40-80° C. and the time is 1-3 hours.
3. The preparation method according to claim 1, characterized in that: The solid content of the pseudo-boehmite slurry is 0.15-0.25; and / or The magnesium oxide slurry is a mixed slurry of magnesium oxide and water, and the solid content of the magnesium oxide slurry is 0.2-0.
4.
4. The preparation method according to claim 1, characterized in that: The surfactant is hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride; and / or The acidic substance is selected from one or more of hydrochloric acid, nitric acid, formic acid and acetic acid; and / or The crystallization reaction is carried out in any one of static, dynamic or intermittent dynamic crystallization.
5. A catalytic cracking catalyst, characterized in that: Taking the total mass of the catalytic cracking catalyst as 100%, the catalyst comprises 5wt% to 25wt% of a molecular sieve on a dry basis, 25wt% to 40wt% of an inorganic oxide binder on an oxide basis, 0 to 3wt% of a rare earth additive on an oxide basis, 5wt% to 15wt% of a magnesium aluminum matrix material on a dry basis, and 30wt% to 50wt% of a modified clay on a dry basis; Wherein, the magnesium-aluminum matrix material is a catalytic cracking aid for reducing coke yield and increasing diesel production obtained by the preparation method of a catalytic cracking aid for reducing coke yield and increasing diesel production as described in any one of claims 1 to 4.
6. The catalytic cracking catalyst according to claim 5, characterized in that The molecular sieve is selected from a Y-type molecular sieve or a modified product of a Y-type molecular sieve, and the modified product of the Y-type molecular sieve is selected from one or more of a REUSY molecular sieve, a HRSY-1 molecular sieve, a RDSY molecular sieve and a MASY molecular sieve.
7. The catalytic cracking catalyst according to claim 5, characterized in that The modified clay is acid-modified clay, and the clay is selected from one or more of kaolin, halloysite, montmorillonite, sepiolite, hydrotalcite and rectorite; and / or The rare earth additive is a water-soluble rare earth compound, preferably one or more of chlorides or nitrates of lanthanum, cerium, praseodymium, neodymium and yttrium; and / or The inorganic oxide binder is one or more of aluminum sol, silica sol, pseudo-boehmite and silica-alumina sol.
8. A method for preparing a catalytic cracking catalyst according to any one of claims 5 to 7, characterized in that: The steps include: 1) adding an inorganic oxide binder to the modified clay and controlling the pH of the system to be 1-3; then adding a magnesium-aluminum matrix material and a molecular sieve to form a slurry; 2) spray drying and calcining the slurry to obtain a solidified catalyst; After washing, the catalytic cracking catalyst is obtained.
9. The preparation method according to claim 8, characterized in that: The process of forming the slurry in step 1) also includes the step of adding a rare earth additive.
10. The preparation method according to claim 8, characterized in that: The calcination and curing temperature is 300-600°C and the time is 0.5-2h; and / or The ammonium chloride aqueous solution is used for washing, and the washing temperature is 30-90° C.; preferably, the mass ratio of the cured catalyst to the ammonium chloride aqueous solution is 1:(2-10), and the mass ratio of ammonium chloride to water in the ammonium chloride aqueous solution is (1-10):100.
Citation Information
Patent Citations
Catalytic cracking catalyst for reducing coke yield and highly producing diesel oil
CN103506148A
Heavy oil catalytic cracking catalyst for enhancing diesel oil yield and preparation method of catalyst
CN103861636A
Fluidized catalytic cracking catalytic promoter with low coke yield and preparation method of fluidized and cracking catalytic promoter
CN104492472A
Preparation method of catalytic cracking aid containing pseudo-boehmite
CN106040217A
Catalytic cracking catalyst capable of improving coke selectivity and preparation method of catalytic cracking catalyst
CN109304205A